In Hospital Mortality and Short-Term Outcomes of Acute Ischemic Stroke Patients Contracting SARS CoV-2 Infection: Experience from a Dedicated Stroke Unit in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: The influence of COVID-19 on in hospital mortality and short-term outcome of acute ischemic stroke is not well known.Objective: The purpose of the present study was to analyze the overall impact of COVID-19 patients and 30-day outcomes of acute ischemic stroke patients.Methodology: This was a hospital-based case-control study from February to May 2021 conducted in stroke unit of National Institute of Neurosciences and Hospital. Consecutive ischemic stroke patients contracting COVID-19 infection was considered as case group and similar patients, negative for SARS CoV-2 on RT-PCR from nasal swab were considered for control group following the inclusion and exclusion criteria.Results: A total number of 50 cases and 99 similar control were taken. Although a significant proportion of control group were male (76.8% vs 50%), there was similar age distribution in both groups. Diabetes and Multiple comorbid conditions and lymphopenia were significantly (p value of